What are parents' preferences for Human Papillomavirus vaccination promotion messages and communication? Application of a discrete choice experiment to a French Caribbean setting - Frédérique G. E. Dorleans; Jonathan Sicsic; Valérie Henry; Isabelle Bonmarin; Gwladys Nadia Gbaguidi; Lucie Leon; Jocelyn Raude; Jacques Rosine; Judith E. Mueller (BMC Public Health)
Abstract Introduction Human Papillomavirus (HPV) vaccine uptake in the French Caribbean has remained below 25% since introduction in 2007, which is well behind national and international targets. Using a discrete choice experiment (DCE), we explored parental preferences around HPV vaccination and optimized communication content in a sample of parents of middle-school pupils in Guadeloupe. Methods We conducted a cross-sectional survey in public and private middle age schools in Guadeloupe in June 2023 using an online questionnaire. Across a series of nine hypothetical scenarios, participants were asked to decide to vaccinate or not and how certain they were about this choice. Scenarios differed by five attributes (diseases characteristics, vaccine safety, health professionals or institutions promoting vaccination, social conformity and optimal vaccination age). We used random effect logit and linear regression models to estimate the effects of attribute levels on vaccine acceptance and vaccine eagerness. Results A total of 389 parents out of the 23,184 pupils’ parents completed the DCE survey. The attributes with a significant effect size on theoretical vaccine acceptance were "social conformity" and "optimal vaccination age”. Overall, the odds of scenarios stating high vaccine coverage in adolescents were at least 1.8 (95% CI: 1.2—2.6) times more likely to yield theoretical vaccine acceptance compared to a low vaccine uptake reference. The odds of providing scientific explanation along with age yielded theoretical vaccination acceptance respectively up to 3.2 times higher (95% CI: 1.7 to 6.1) in parents reporting an un vaccinated child and not intention to vaccinate. For vaccine eagerness, we observe significant positive effects of communication content overall when stating high vaccination uptake in adolescents or scientific evidence along with age or mentioning cancer prevention. Parents always refusing vaccination remained unsensitive to communication contents. Discussion and conclusion These original DCE results highlighted the need for tailoring specific HPV vaccination promotion communication in a French Caribbean setting. Contextual features such as sexuality concerns as regard to age and peers’ adhesion to vaccination have to be thoroughly considered. The nationwide HPV vaccination campaign in middle schools should adapt communication in order to raise HPV vaccine uptake in the French Caribbean.